New perspectives on Microsoft Office Excel 2003 - June Jamrich Parsons (Thomson/Course Technology, 2006)
Part of the New Perspectives series, this text offers a case-based, problem-solving approach and innovative technology for meaningful learning of Microsoft Excel 2003